The Effect of Fitness Level, Organizational Support, and Compensation on the Work Productivity of Tangerang City Health Office Employees Mediated by Organizational Motivation - Suwardiman; Hadiwijaya, Dudung; Muttaqin, Imam (International Journal of Science and Society, 2024)
Work productivity is one of the important factors in organizational success. In the health sector, employee work productivity has a very important role in providing quality health services to the community. The purpose of this study was to analyze the effect of body fitness level, organizational support, and compensation on the work productivity of Tangerang City Health Office employees mediated by organizational motivation. This research uses quantitative research methods. Data collection techniques in this study used literature study and questionnaire methods. The data that has been collected is then analyzed using regression analysis. The results showed that the level of body fitness, organizational support, and compensation had a positive effect on the work productivity of employees of the Tangerang City Health Office. Then, organizational motivation is proven to mediate the influence of body fitness level, organizational support, and compensation on the work productivity of Tangerang City Health Office employees.